Proarrhythmia risk prediction using human induced pluripotent stem cell-derived cardiomyocytes - Daiju Yamazaki; Takashi Kitaguchi; Masakazu Ishimura; Tomohiko Taniguchi; Atsuhiro Yamanishi; Daisuke Saji; Etsushi Takahashi; Masao Oguchi; Yuta Moriyama; Sanae Maeda; Kaori Miyamoto; Kaoru Morimura; et al. (Elsevier, 2018)
Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are expected to become a useful tool for proarrhythmia risk prediction in the non-clinical drug development phase. Several features including electrophysiological properties, ion channel expression profile and drug responses were investigated using commercially available hiPSC-CMs, such as iCell-CMs and Cor.4U-CMs. Although drug-induced arrhythmia has been extensively examined by microelectrode array (MEA) assays in iCell-CMs, it has not been fully understood an availability of Cor.4U-CMs for proarrhythmia risk. Here, we evaluated the predictivity of proarrhythmia risk using Cor.4U-CMs. MEA assay revealed linear regression between inter-spike interval and field potential duration (FPD). The hERG inhibitor E−4031 induced reverse-use dependent FPD prolongation. We next evaluated the proarrhythmia risk prediction by a two-dimensional map, which we have previously proposed. We determined the relative torsade de pointes risk score, based on the extent of FPD with Fridericia's correction (FPDcF) change and early afterdepolarization occurrence, and calculated the margins normalized to free effective therapeutic plasma concentrations. The drugs were classified into three risk groups using the two-dimensional map. This risk-categorization system showed high concordance with the torsadogenic information obtained by a public database CredibleMeds. Taken together, these results indicate that Cor.4U-CMs can be used for drug-induced proarrhythmia risk prediction. Keywords: Early afterdepolarization, hiPSC-CMs, Microelectrode array, Proarrhythmia, Safety assessment